Association between rheumatoid arthritis and atrial fibrillation: a new perspectives - Rea, Marcos Velasco; Velasco, Steveen Ayala; Andrade, Milipsa Pozo; Lozada, Carlos Cruz; Torres, Jeremy Calderón; Chávez, Irene Cervantes; Gálvez, José Castillo; Velastegui, Steven Suárez (International Journal of Research in Medical Sciences, 2025)
Rheumatoid arthritis (RA) is a disease with an autoimmune component that directly and indirectly affects various organs, causing significant damage and complications. However, knowledge about the subject and its association with atrial fibrillation (AF) is limited, making its study important due to its close relationship with the incidence of acute coronary syndrome (ACS). AF is the most common cardiac arrhythmia worldwide, showing a significant increase in morbidity and mortality in people who suffer from it. RA characterized by being a systemic inflammatory disease, affects 0.5-1.0% of the adult population. It is associated with a higher incidence of cardiac arrhythmias such as AF. Several epidemiological studies find that the risk of AF is increased in RA compared to the general population. Considering that inflammation plays an important role in AF, RA may be involved in the onset and development of AF. This review summarizes the epidemiology, pathophysiology, and management of AF in patients with RA.